Wealth and tourism in Thailand: A spatial analysis using google maps - Nichapat Sangkaew; Aziz Nanthaamornphong; Chayanon Phucharoen (Social Sciences and Humanities Open)
This study investigated the relationship between community wealth and the tourism industry. We used geospatial analysis and User Generated Content from Google Maps to examine the distribution and density of tourist accommodations and attractions on a 2.4 km grid scale. Surprisingly, we found that there was no significant correlation between community wealth and attraction density, suggesting that increasing attractions may not necessarily lead to greater community wealth. However, a more pronounced 4.2% positive correlation was observed between wealth and accommodation density, indicating that expanding accommodation options can boost local economies. Notably, our data suggests that around 1% of communities in Thailand, represented by 66,659 grids, may be nearing a plateau in terms of tourism income, a phenomenon we term “tourism income saturation.” Our research highlights the importance of hospitality ventures within communities, rather than just attractions, in driving local economic growth. Our innovative methodology, based on extensive datasets, contributes to understanding the grassroots impact of tourism, benefiting both academic discourse and industry decision-makers. While innovative, this approach has limitations, including reliance on digital footprints and challenges in establishing causality. This research offers actionable insights for policymakers aiming to balance tourism development.